2021
DOI: 10.3390/biomedicines9091135
|View full text |Cite
|
Sign up to set email alerts
|

Decreased MicroRNA-150 Exacerbates Neuronal Apoptosis in the Diabetic Retina

Abstract: Diabetic retinopathy (DR) is a chronic complication associated with diabetes and the number one cause of blindness in working adults in the US. More than 90% of diabetic patients have obesity-associated type 2 diabetes (T2D), and 60% of T2D patients will develop DR. Photoreceptors undergo apoptosis shortly after the onset of diabetes, which contributes to the retinal dysfunction and microvascular complications leading to vision impairment. However, how diabetic insults cause photoreceptor apoptosis remains unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Retinal ganglion and amacrine cells are the first neurons in which hyperglycemia induces apoptosis ( 20 ). Photoreceptor cells in the diabetic retina also die through apoptosis and calpain activation ( 21 , 22 ). Several animal models have been developed to study the molecular basis of DR pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Retinal ganglion and amacrine cells are the first neurons in which hyperglycemia induces apoptosis ( 20 ). Photoreceptor cells in the diabetic retina also die through apoptosis and calpain activation ( 21 , 22 ). Several animal models have been developed to study the molecular basis of DR pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…We previously showed that miR-150 −/− -T2D mice have more severe inflammation in photoreceptors and exacerbated vascular degeneration compared with the WT-HFD mice [ 142 ]. Since the biological processes mediated by microRNAs and their targets are often tissue- and cell-type-dependent as stated earlier [ 152 , 195 ], after screening the top 30 predicted target genes of miR-150 [ 113 , 193 ] and identifying new bona fide targets that are pro-inflammatory [ 113 ], multiple transcription factors including the eukaryotic translation termination factor 1 ( Etf1 ), early growth response 1 ( Egr1 ), MYB proto-oncogene ( Myb ), and ETS-domain transcription factor 1 (Elk1) were found to be expressed in retinal photoreceptors and endothelial cells [ 196 ]. Downregulation of miR-150 correlates with an upregulation of Etf1 , Egr1 , Myb , and Elk1 and pro-inflammatory cytokines, while overexpression of miR-150 or knocking down any of these transfection factors decrease the expression of pro-inflammatory cytokines in cultured adipose B lymphocytes [ 113 ].…”
Section: Microrna-150 and Drmentioning
confidence: 99%
“…Using cultured murine photoreceptors treated with palmitic acid (PA) to mimic obesity-associated T2D, we found that PA elicited an increase of phosphorylated NF-ĸB (pP65), an inflammation marker, which persisted for 24 h and correlated with a persisting decrease of miR-150 and increase of Elk1 . However, PA elicited only temporary increases of Etf1 , Egr1 , or Myb , although these three transcription factors are direct downstream targets of miR-150 and expressed in the neural retina [ 196 ]. Overexpression of miR-150 or knocking down Elk1 not only decreased the expression of ELK1 (protein) but also relieved PA-induced increase of inflammation.…”
Section: Microrna-150 and Drmentioning
confidence: 99%
See 2 more Smart Citations